Modelling and computer simulation studies of sugar based amphiphilic systems / Sara Ahmadi - Ahmadi, Sara (2014)
Nowadays, sugar-based amphiphiles are among the most attractive class of compounds to be studied both fundamentally and application-wise. They are one of the main components in cell membranes and play important role in many biological functions. Therefore, understanding the nature of the different liquid crystal phases of these materials is important and conceivable using different experimental techniques, theory and simulation. This thesis focuses on the last two methods to investigate the properties of these highly interesting soft materials. We begin by examining a set of novel glycolipids which has been modified to include crown ethers attached to the sugar ring which increases the size of the hydrophilic area and causes to have higher packing parameters. Higher packing parameters induced formation of nonlamellar phases and prevent formation of lamellar phases. A theoretical study of a series of five glucose based glycolipid crown ethers and their complexes with Na+ and K+ was performed using the density functional theory with B3LYP/6-31G*. Optimized geometrical structures of the glycolipid crown ethers with cations were obtained and their corresponding electronic properties were calculated. In general, it was found that the oxygen atoms pairs O2 and O3 (or O4 and O6) on the sugar ring are constrained from moving toward the cation, which results in a weaker O-cation coordination strength for the oxygen pair compared to the other oxygen atoms in the crown ether ring. The thermodynamic properties of the binding of the complexes and the exchange reaction in gas phase were evaluated. The cation selectivity pattern among the five molecules was in good agreement with the experiment. Fully atomistic molecular dynamics simulation studies of thermotropic bilayers were performed using a set of glycosides namely n-octyl-β-Dglucopyranoside (β-C8Glc), n-octyl-α-D-glucopyranoside (α-C8Glc), n-octyl-β-Dgalactopyranoside (β-C8Gal) and n-octyl-α-D-galactopyranoside (α-C8Gal) to investigate the stereochemical relationships of the epimeric/anomeric quartet liner glycolipids with the same octyl chain group. The results showed that, the anomeric stereochemistry or the axial/equatorial orientation of C1-O1 (α/β) is an important factor controlling the area and d-spacing of glycolipid bilayer systems in the thermotropic phase. The C4-epimeric (axial/equatorial)stereochemistry becomes dominant together with the anomeric one for the inter-molecular hydrogen bond. Thus, the trend in hydrogen bonding goes as β-C8Gal> α-C8Glc> β-C8Glc> α- C8Gal. The four bilayer systems showed anomalous diffusion behaviour with an observed trend for the diffusion coefficient exponent (α-C8Gal > β-C8Glc > α- C8Glc > β-C8Gal), and was in the reverse order to the hydrogen bonding interaction strength, but in compliance to the cis-trans effect of the C4-epimer and anomer. We have also studied the lyotropic reverse hexagonal phase HII from a glycolipid, namely using the Guerbet branched-chain (2’n-octyl-n-dodecyl)-β-Dglucopyronoside( C8C12β-D-Glc),at 14% and 22% water concentrations. In this simulation, it is necessary for us to use the united atom force field for carbohydrate from GROMOS because this approach will overcome the ambiguity of two optical stereoisomers arising from the chiral center at the Guerbet branched chain. Moreover, this force field will enable us to run a longer simulation. Our simulations showed that at low water concentration (14%) the sugar head group overlapped extensively and protruded into the water channel. In contrast, in the 22% concentration system, a water column free from the sugar head group was formed, as expected for the system close to the limit of maximum hydration. In both concentrations, we found anomalous water diffusion in the xy-plane, i.e. the twodimensional space confined by the surface of the cylinder. On the other hand, in the z-axis, the water diffusion obeyed the Einstein relation for 22% system, while for the 14% system it was slightly anomalous. Generally, a higher probability of hydrogen bonding but a shorter lifetime was found for the system of 22% water compared to the system of 14% water.